Electricity production from biomass in Nigeria: options, prospects and challenges (2013)
Biomass power, also called bio power, is electricity produced from biomass fuels. Biomass consists of plant materials and animal products. Biomass fuels include residues from food production and processing, trees and grasses grown specifically as energy crops, and gaseous fuels produced from solid biomass and wastes. This paper highlights the various biomass materials available in the country and the available technologies that are used for converting biomass to electricity. The paper also highlights the broad policy objectives of government with regards to the development of renewable energy in general and biomass development in particular. The paper concludes by exploring based on global experiences and best practices, the various options, and their resulting prospects and challenges in producing electricity from biomass. The paper highlighting the fact that though the prospects of using biomass for electricity generation is high; land availability, plant location, scale and choice of technology and distribution of economic benefits are factors that have to be considered in deploying biomass for electricity generation in Nigeria.